Determinan Tax Avoidance di Indonesia, Malaysia, dan Singapura - Muhammad Arif Wicaksono; Siti Hartinah (Economic Reviews Journal, 2025)
For tax authorities in a number of nations, including Singapore, Malaysia, and Indonesia, tax evasion is still a major problem. This study examines the effects of capital intensity, inventory intensity, and related party transactions on tax evasion in the real estate and property industries in these three nations. Secondary data from business financial statements for the 2019–2023 period, obtained from official stock market platforms and pertinent corporate filings, is used in the study. Using a purposive sampling technique, a final sample of 25 businesses was obtained. Regression analysis of panel data was performed with E-Views 12. The findings show a favorable and statistically significant impact of related party transactions on tax evasion. Tax avoidance, on the other hand, is positively but statistically insignificantly correlated with both capital intensity and inventory intensity. Based on these results, it appears that related transactions have a greater influence on tax evasion behavior than inventory control or asset structure. Policymakers, corporate managers, and investors may all benefit from this research's useful insights into the main factors that influence tax evasion. The cross-country emphasis of this study within the property and real estate industry, an area that has not gotten much attention in previous empirical research, is what makes it innovative.